2012
DOI: 10.1073/pnas.1213897109
|View full text |Cite
|
Sign up to set email alerts
|

Human mitochondrial holocytochrome c synthase’s heme binding, maturation determinants, and complex formation with cytochrome c

Abstract: Proper functioning of the mitochondrion requires the orchestrated assembly of respiratory complexes with their cofactors. Cytochrome c , an essential electron carrier in mitochondria and a critical component of the apoptotic pathway, contains a heme cofactor covalently attached to the protein at a conserved CXXCH motif. Although it has been known for more than two decades that heme attachment requires the mitochondrial protein holocytochrome c synthase (HCCS), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
163
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(177 citation statements)
references
References 75 publications
13
163
1
Order By: Relevance
“…In the case of the Slo1 channels (12), a cytochrome c-like CXXCH motif has been implicated (12,28). However, this raises immediate questions that do not chime with established patterns of behavior in other heme proteins, because most proteins bind heme reversibly (i.e., noncovalently), whereas cytochrome c uses complex and specialized biosynthetic machinery to bind heme irreversibly (i.e., covalently) through thioether bonds from the Cys residues of the CXXCH motif to the heme vinyl groups (29,30). There is as yet no evidence that ion channels proteins use similarly specialized biosynthetic machinery; thus, it seems unlikely that their heme is covalently attached.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the Slo1 channels (12), a cytochrome c-like CXXCH motif has been implicated (12,28). However, this raises immediate questions that do not chime with established patterns of behavior in other heme proteins, because most proteins bind heme reversibly (i.e., noncovalently), whereas cytochrome c uses complex and specialized biosynthetic machinery to bind heme irreversibly (i.e., covalently) through thioether bonds from the Cys residues of the CXXCH motif to the heme vinyl groups (29,30). There is as yet no evidence that ion channels proteins use similarly specialized biosynthetic machinery; thus, it seems unlikely that their heme is covalently attached.…”
Section: Discussionmentioning
confidence: 99%
“…Previous genetic studies have shown that bacterial cytochromes are incompatible substrates for HCCS-mediated maturation (25,27,28,30). However, it has also been shown by two independent groups that making three mutations in the N-terminal ␣ helix-1 region of bacterial cytochromes can convert them into a substrate that is recognized and matured by HCCS (27,28).…”
mentioning
confidence: 99%
“…However, it has also been shown by two independent groups that making three mutations in the N-terminal ␣ helix-1 region of bacterial cytochromes can convert them into a substrate that is recognized and matured by HCCS (27,28). c-type cytochromes from the alphaproteobacteria Rhodobacter and Paracoccus have glutamate residues at the sequence positions equivalent to Lys 8 and Ile 10 found in human cyt c (see Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations